Covariance structures of fat and protein influence the estimation of IgG in bovine colostrum. Issue 1 (12th February 2016) - Løkke, Mette Marie; Engelbrecht, Rikke; Wiking, Lars
Abstract : On-farm instruments for assessing colostrum quality are needed in order to ensure that the calf is supplied with enough IgG to avoid failure of passive transfer. The aim of this study was to evaluate methods for estimating the IgG concentration in cows' colostrum. This research included 126 colostrum samples from 21 Danish farms with different breeds, ensuring a broad variation pattern in IgG, total protein and fat concentration. Approximately one third of the samples did not fulfil the recommendation of >50 g IgG/l colostrum, and the IgG concentration decreased with time from calving to milking. The ratio of IgG to total protein varied from 6 to 61%, however IgG and total protein were correlated with r 2 = 0·70. The variation in fat was independent of variations in protein and IgG. The IgG concentration was measured by ELISA and compared to fast measurements by specific gravity by colostrometer, Brix by refractometer and prediction from infrared spectroscopy. The three fast methods were all correlated to the total protein concentration of colostrum; however specific gravity was also influenced by the fat concentration. Furthermore, specific gravity generally overestimated the IgG concentration, and the cut-off level should be raised to 1050 in order to ensure adequate IgG in colostrum. None of the methods estimated IgG concentration better than the correlation of total protein and IgG, meaning that they all depended on the indirect correlation between total protein and IgG. The results suggest that using a refractometer for quality control of colostrum is an easy and feasible method, and a cut-off level of Brix 22 seems sufficient to assure adequate IgG concentration in colostrum fed to the calf.